2019
DOI: 10.1111/clr.13550
|View full text |Cite
|
Sign up to set email alerts
|

Abutment screw withdrawal after conical abutment settlement: A pilot study

Abstract: Objective This study investigated the effects of abutment screw withdrawal after conical abutment settlement on the stability of the implant–abutment connection. Materials and methods Twenty implants of a conical connection system were used. Two two‐piece abutment designs were used: cone only (n = 10; NI) and cone plus octagonal index design (n = 10; I); for each design, five samples were used with (S) and without (NS) abutment screw withdrawal before a cyclic test. Finally, four groups, namely Gr S(NI), Gr S(… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 26 publications
(33 reference statements)
0
9
0
Order By: Relevance
“…114 When an octagonal index was added to the abutments, the bending strength was reduced, and wear, plastic deformation, and fractures were found under SEM. 113,114 Furthermore, marked fritting wear was reported around the edges of the antirotational index. 113,114 In summary, no perfect implant shoulder geometry is able to avoid some micromotion at the implant-abutment level.…”
Section: Bone Cellsmentioning
confidence: 99%
See 2 more Smart Citations
“…114 When an octagonal index was added to the abutments, the bending strength was reduced, and wear, plastic deformation, and fractures were found under SEM. 113,114 Furthermore, marked fritting wear was reported around the edges of the antirotational index. 113,114 In summary, no perfect implant shoulder geometry is able to avoid some micromotion at the implant-abutment level.…”
Section: Bone Cellsmentioning
confidence: 99%
“…113,114 Furthermore, marked fritting wear was reported around the edges of the antirotational index. 113,114 In summary, no perfect implant shoulder geometry is able to avoid some micromotion at the implant-abutment level.…”
Section: Bone Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…Apart from the index design, a screwless conical connection design has been demonstrated clinical success [27], however, lower mechanical resistance was observed when compared with the screw-retained conical connection design [28]. Recently, the feasibility of abutment screw withdrawal after conical abutment settlement was evaluated to solve the difficult problems of screw loosening and screw fracture [29]. Although the conical implant-abutment connection system with index design passed the cyclic test, additional studies should be conducted to test the clinical feasibility [29].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the feasibility of abutment screw withdrawal after conical abutment settlement was evaluated to solve the difficult problems of screw loosening and screw fracture [29]. Although the conical implant-abutment connection system with index design passed the cyclic test, additional studies should be conducted to test the clinical feasibility [29]. Furthermore, Shash et al reported that a novel one-piece implant structure could enhance the biomechanical stability of implant-bone system due to no implant-abutmentscrew joint [30]; yet they are not commonly used for broad implants.…”
Section: Introductionmentioning
confidence: 99%